Answer:
The correct option is;
f(x) = {x - 1 if -3 ≤ x < 1 f(x) = {-3·x + 9, if 2 ≤ x ≤ 4
Explanation:
The given coordinates of the points are;
For the first segment
Beginning point [-3, -4] (inclusive)
Endpoint (1, 0), (noninclusive)
For the second segment
Beginning point [2, 3] (inclusive)
Endpoint [4, -3] (inclusive)
The equation of the first segment is therefore;
y - 0 = (0 + 4)/(1 + 3)×(x - 1) = 1 × (x - 1)
y = x - 1
The equation of the second segment is found as follows;
y + 3 = (-3 - 3)/(4 - 2)×(x - 4) = -3 × (x - 4)
y + 3 = -3 × (x - 4) = -3·x + 12
y = -3·x + 12 - 3 = -3·x + 9
Therefore, we have;
f(x) = {x - 1 if -3 ≤ x < 1 and f(x) = {-3·x + 9, if 2 ≤ x ≤ 4